(untitled) (Journal of Pathology of Nepal, 2016)
Background: Skin Appendageal tumors are a large and diverse group of tumors that are commonly classiied according to their state of appendageal differentiation: follicular, sebaceous, eccrine and apocrine. Objectives of this study were to study the clinic-epidemiological proile of skin appendageal tumors and to correlate the clinico-histopathological diagnosis. Materials and Methods: This was a retrospective and prospective study which included all cases of skin adnexal tumours diagnosed histologically during the period of four and half years. Tumors were analyzed considering the anatomic location, duration, size and type of the tumour, along with age and sex of the patient. The Histological characterization was done according to the WHO classiication system and was correlated with the clinical diagnosis. Collected data were analysed using SPSS PC+ 11.5 Version for statistical analysis. Results: A total of 70 neoplasms of skin appendages included, 68 (97.1%) were benign and 2 (2.9%) was malignant. Female comprised of 47 (67.1%) and 23 (32.9%) were male. The mean age was 39.23 years. Of all, 43 (61.4%) tumors were follicular, 18 (25.7%) were eccrine, 7 (10%) were apocrine and 2 (2.9%) were with sebaceous differentiation. The three commonest tumors encountered in this study were Pilomatricoma (21.4%), Keratoacanthoma (17.1%) and Trichoepithelioma (14.3%). Clinically, 13/70 (18.5%) cases were diagnosed as SAT. Conclusion: Taking histologic diagnosis as gold standard, clinical diagnosis was found to have a sensitivity of 11.08% and speciicity of 77.9 %. Histopathology is highly signiicant to diagnose SAT (p <0.011).